Kebijakan Sertifikasi Guru dan Kendalanya dalam Meningkatkan Profesionalisme di MA Syaikh Zainuddin NW Anjani Lombok Timur - Ittihad Ittihad (LP2M STIT Palapa Nusantara, 2023)
This study aims to find out the problems and analyze the needs of teachers in Madrasah Aliyah Shaykh Zainuddin Nahdlatul Wathan Anjani after certification. This research uses descriptive research with quantitative data analysis techniques (in the form of descriptive statistics), and qualitative techniques (in the form of descriptions/narratives in the form of words and sentences). Data collection techniques using interviews, documentation and open questionnaires. The results show that teacher certification has an impact on increasing teacher competence, where the competence of teachers who have been certified is in a better category than those who have not been certified, although independent efforts are still not maximal for increasing professionalism. In addition, problems were found in terms of the incompatibility of the number of teachers compared to the needs of teachers in certain subjects, so that there were obstacles in fulfilling the minimum 24 hour teaching load, which was one of the conditions for receiving professional allowances.